An Extremely Rare Case of Thoracic Intramedullary Melanocytoma: Case Report and Review of Literature - Ruggeri AG; Mancarella C; Dugoni DE; Landi A; Delfini R (Journal of Brain And Spinal Cancer, 2014)
Melanocytoma is a rare benign lesion arising from leptomeningeal melanocytes. Meningeal melanocytomas are commonly seen in the thoracic region of the spinal canal and may also arise in the cervical or lumbar region, most often located in the intradural extramedullary compartment 1. To our knowledge, only 21 cases of intramedullary melanocytomas have been reported in the literature to date. The authors present a rare case of thoracic intramedullary melanocytoma and the review of the literature pointing out the role of diagnosis, surgical treatment and follow-up.
Keywords: melanocytoma